"Taking the ghetto out of the dog:" reproducing inequality in pit bull rescue. Issue 10 (8th August 2020) - Guenther, Katja M.
ABSTRACT: This paper examines how rescuers of pit bulls in the Los Angeles area participate in remaking pit bulls so that the dogs shed their racialized, gendered, and classed identities as companions to Black and poor Latinx men and instead become suitable companions for white, feminized middle-class homes. Pit bull rescuers employ a range of strategies to make the dogs more palatable to the types of adopters rescuers see as desirable, and help reinforce rescuers' construction of whiteness as morally superior vis-à-vis non-human animals. Even as they work to save individual dogs, rescuers of pit bulls leave intact beliefs that the dogs' previous guardians were problematic and fail to challenge the social structures that lead the dogs into the shelter.